First record of the cicada genus Karenia Distant, 1888 (Hemiptera: Cicadidae) from Vietnam, with description of a new species - Thai, Pham Hong; Yang, Jeng-Tze (Zootaxa, 2012)
The first record of the genus Karenia Distant, 1888 from Vietnam is presented. Karenia hoanglienensis sp. nov. (Hemiptera: Cicadidae) is described from Lao Cai Province, northern Vietnam. Photographs of an adult male, illustrations of the male genitalia, a distribution map and biological data for K. hoanglienensis sp. nov. are provided.